1983
DOI: 10.1677/joe.0.0990469
|View full text |Cite
|
Sign up to set email alerts
|

Steroid production in vitro by rat ovaries during sexual maturation

Abstract: To determine changes in steroidogenesis by rat ovaries during sexual maturation, ovaries obtained at various ages (days 10-35) and at the first pro-oestrus were incubated in the absence or presence of LH and the accumulation of steroids in the medium was measured. Basal and LH-stimulated oestradiol-17 beta and testosterone release into the medium, expressed in pmol/4 h per mg ovary, was high at day 10 of age and at first pro-oestrus. Between days 20 and 35 basal oestradiol and testosterone release was low and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…From these results it is clear that the pattern of ovarian metabolism in the mouse during development differs from that in the rat, particularly in the production of C19 steroids. In the rat, accumulation of androstenedione and testosterone is very low or non-detectable during development (Karakawa et al, 1976;Uilenbroek et al, 1983), the major products being androsterone and androstanediol which show a peak of production around the first ovulation (Eckstein et al, 1970;Karakawa et al, 1976;Inaba et al, 1978;Suzuki et al, 1978;Uilenbroek et al, 1983). There was a peak in 5a-reductase activity in the mouse ovary between 7 and 38 days judged by the accumulation of 5a-reduced C21 steroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From these results it is clear that the pattern of ovarian metabolism in the mouse during development differs from that in the rat, particularly in the production of C19 steroids. In the rat, accumulation of androstenedione and testosterone is very low or non-detectable during development (Karakawa et al, 1976;Uilenbroek et al, 1983), the major products being androsterone and androstanediol which show a peak of production around the first ovulation (Eckstein et al, 1970;Karakawa et al, 1976;Inaba et al, 1978;Suzuki et al, 1978;Uilenbroek et al, 1983). There was a peak in 5a-reductase activity in the mouse ovary between 7 and 38 days judged by the accumulation of 5a-reduced C21 steroids.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian steroid metabolism during development in the rat has been studied in several laboratories by measuring the metabolites formed from exogenous tritiated progesterone (Eckstein et ai, 1976;Karakawa et al, 1976;Eckstein & Ravid, 1979;Uilenbroek et al, 1983;Cohen et al, 1984). In contrast, few studies have been carried out to examine steroidogenesis in the mouse ovary although this animal offers distinct advantages in the study of ovarian development.…”
Section: Introductionmentioning
confidence: 99%
“…In pubertal rats a similar divergence between content and release might account for the discordance between the steady level of ovarian ILA content and the decline in serum FSH concentration in the period between days -10 and -6, although this may also be explained in part by assuming increasing responsive¬ ness of the pituitary to ILA-mediated suppression of FSH secretion (Hermans, van Leeuwen, Debets & de Jong, 1980). Various studies suggest that the decline of serum FSH concentration over this period cannot be attributed to increased suppression through ovarian steroids (Meijs-Roelofs et al 1981Uilenbroek, Woutersen & van der Linden, 1983). In the present study oestradiol levels showed little change over the period from day -10 to day -3 (<40ng/l) and a significant increase to levels^50 ng/1 was only found on days -2 and -1 (unpublished results from our laboratory).…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of 5a-androstane-3a,i7ß-diol in the ovary were determined as described earlier (Uilenbroek et al 1983). Cross-reactivity of MEP with the androstanediol antiserum was 0.2%.…”
Section: Hormone Assaysmentioning
confidence: 99%
“…The activity of this enzyme decreases before the first ovulation (Eck¬ stein & Lerner 1977;Uilenbroek et al 1983;Meijs-Roelofs et al 1985). It has been suggested that the decrease of this enzyme activity might play a role in the onset of the first ovulation (Ruf 1983).…”
mentioning
confidence: 99%